EFFECT OF ELECTRIC FIELD ON SEED GROWTH OF FIVE CYAMOPSIS TETRAGONOLOBA GENOTYPES - DR.SURESHBABU (Global Journal of Plant and Soil Sciences, 2024)
The study aimed to investigate the effect of the application of external electric field on the seed germination and growth of five genotypes of Cyamopsis tetragonoloba L. plant (Gm2, Gm5, Gm6, Gm8 and Gm34). This effect is expressed in terms of electric energy density created within pairs of copper plates forming electric capacitors in a DC current circuit connected to an electric source. The system was designed and used for experimentation with two copper plate's area (25 and 225 cm2) and different voltage levels (0, 6, 9, 22.1 and 30 volts). Seeds of C. tetragonoloba were located within spaces between each capacitor’s plates and are were exerted upon by different energy densities. The results showed that when five treatments (0, 6, 9, 22.1 and 30 volts) were used to the five genotypes in 12 days after treatments; all treatments resulted in inhibition of root growth and plant height in the germinating seeds either when 25 cm2 or 225 cm2 plate's area were used. Also, when 25 cm2 and 225 cm2 plate's area were used with one treatment of 6 volts for the five genotypes; 225 cm2 plates were found more affective in the reduction of plant height than 25 cm2 plates. When 25 cm2 plates were used the highest reduction of radicle length was obtained by 9 volts. When the five genotypes were exposed to 6 volts by using 225 cm2 plates; the genotype that was affected by the treatment in reducing radicle length was Gm2 in 3rd and 4th day after treatment. The less affected one was Gm5. The results suggested that electric field has direct effect on seed germination and development of C. tetragonoloba plants.